Penyuluhan Hama dan Penyakit pada Tanaman Padi dan Hortikultura di Desa Cihamerang, Sukabumi - Istikorini, Yunik; Rohmah, Sabila Nur; Maulina, Alaysha; Fiqri, Muhammad; Fortunata, Maura Rezky; Sutanto, Vallari Kalea Ananda; Ardian, Dava Putra; Navizan, Fadhli Zhafran; Alam, Ilham Fatkhy (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The majority of Cihamerang Village residents are horticultural farmers. One of the challenges faced by them is pest and disease attacks. Cihamerang Village farmers overcome this by uprooting infected plants and using chemical pesticides which of course can have a negative impact if done continuously. Therefore, counseling on plant pests and diseases in the form of applying the use of botanical pesticides and eco enzyme as a substitute for the use of chemical pesticides, is one alternative to overcome these challenges. This extension aims to increase farmers' knowledge and understanding of the types of diseases and plant pest organisms (OPT) in rice and horticultural crops and how to control them. The methods used were counseling, discussion, demonstration, and evaluation. Counseling was conducted using the lecture method. The material provided was related to the identification of pests and plant diseases, how to control pests and plant diseases, how to make botanical pesticides, and how to make eco enzyme. Discussions were held between farmers and academics and agricultural experts. Demonstrations were conducted to improve farmers' skills in making botanical pesticides and eco enzyme. The evaluation results showed that this activity increased the knowledge of Cihamerang Village farmers related to pests and plant diseases, as well as the manufacture of botanical pesticides and eco enzyme.